2011
DOI: 10.1002/stem.624
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Promotes Neuronal Differentiation from Mesenchymal Stem Cells Through Activation of Tlx3

Abstract: Wnt/β-catenin signaling promotes neural differentiation by activation of the neuron-specific transcription factors, Neurogenin1 (Ngn1), NeuroD and Brn3a, in the nervous system. Since neurons in cranial sensory ganglia and dorsal root ganglia transiently express Ngn1, NeuroD and Brn3a during embryonic development, we hypothesized that Wnt proteins could instructively promote a sensory neuronal fate from mesencymal stem cells (MSCs) directed to differentiate into neurons. Consistent with our hypothesis, Wnt1 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 54 publications
3
75
0
Order By: Relevance
“…A recent publication revealed that Wnt1 factor induces Tlx3 expression, which was correlated with neuronal differentiation ability of MSC [19]. Wnt1 is a developmentally important gene involved in intercellular signaling that is expressed by CGNs in newborn mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication revealed that Wnt1 factor induces Tlx3 expression, which was correlated with neuronal differentiation ability of MSC [19]. Wnt1 is a developmentally important gene involved in intercellular signaling that is expressed by CGNs in newborn mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that RA combined with other factors, such as NGF, β-ME, BDNF, Forskolin, and IBMX, is necessary for the neural differentiation of MSCs in vitro (29)(30)(31). In the present study, it was found that after the combined treatment with a low concentration of RA, more than 30% of hUCB-MSCs were differentiated into GFAPexpressing cells.…”
Section: Discussionsupporting
confidence: 53%
“…Canonical Wnt signaling, due to ␤-catenin activation, promotes axonal guidance, neuronal differentiation, neuronal connectivity, and cell survival (33,(59)(60)(61). Combining this knowledge with our previous observations that ORF2 expression stimulates neurite formation in cells expressing Notch (42,43), we tested whether ␤-catenin cooperates with ORF2 to stimulate neurite formation in Neuro-2A cells.…”
Section: Expression Of Wnt Antagonists Is Induced During Dex-induced mentioning
confidence: 88%